Optical coherence tomography using images of hair structure and dyes penetrating into the hair. Issue 4 (17th March 2014) - Tsugita, Tetsuya; Iwai, Toshiaki
<x xml:space="preserve">Abstract</x> Background/purpose Hair dyes are commonly evaluated by the appearance of the hair after dyeing. However, this approach cannot simultaneously assess how deep the dye has penetrated into hair. Methods For simultaneous assessment of the appearance and the interior of hair, we developed a visible‐range red, green, and blue (RGB) (three primary colors)‐optical coherence tomography (OCT) using an RGB LED light source. We then evaluated a phantom model based on the assumption that the sample's absorbability in the vertical direction affects the tomographic imaging. Results Consistent with theory, our device showed higher resolution than conventional OCT with far‐red light. In the experiment on the phantom model, we confirmed that the tomographic imaging is affected by absorbability unique to the sample. Furthermore, we verified that permeability can be estimated from this tomographic image. We also identified for the first time the relationship between penetration of the dye into hair and characteristics of wavelength by tomographic imaging of dyed hair. Conclusion We successfully simultaneously assessed the appearance of dyed hair and inward penetration of the dye without preparing hair sections.